Prohibition of Child Recruitment as Soldiers: An International Regulatory Discourse - Arumbinang, Mohammad Hazyar; Gunawan, Yordan; Salim, Andi Agus (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Children are frequently turned into child soldiers or used as human shields in armed conflicts. The use of child soldiers is condemned by all nations and is regarded as a grave breach of both children's rights and international humanitarian law. The paper aims to discuss pertinent provisions of international legal norms, particularly those that relate to child soldiers in the sequence of their adoption. Additionally, it presents the issue of the implementation of several international conventions on the issue of using child soldiers and its atrocities in the international community. As the result, when it comes to addressing the issue of child soldiers, the international legal sources do not present a consistent picture. There has been a various provision in the determination of minimum age of a child that led to major debates among international communities. The situation is further exacerbated by the fact that, while some countries have accepted the convention as binding on themselves, their implementation faces significant challenges, such as the fact that the majority of international treaties lack sanctioning power, limiting their ability to properly accomplish the preventive purpose.